Economics of Contracts; a Premier - Salanie, Bernard (Cambridge, 2005)
The theory of contracts grew out of the failure of the general equilibrium model to account for the strategic interactions among agents that arise from informational asymmetries. This popular text, revised and updated throughout for the second edition, serves as a concise and rigorous introduction to the theory of contracts for graduate students and professional economists. The book presents the main models of the theory of contracts, particularly the basic models of adverse selection, signaling, and moral hazard. It emphasizes the methods used to analyze the models, but also includes brief introductions to many of the applications in different fields of economics. The goal is to give readers the tools to understand the basic models and create their own. For the second edition, major changes have been made to chapter 3, on examples and extensions for the adverse selection model, which now includes more thorough discussions of multiprincipals, collusion, and multidimensional adverse selection, and to chapter 5, on moral hazard, with the limited liability model, career concerns, and common agency added to its topics. Two chapters have been completely rewritten: chapter 7, on the theory of incomplete contracts, and chapter 8, on the empirical literature in the theory of contracts. An appendix presents concepts of noncooperative game theory to supplement chapters 4 and 6. Exercises follow chapters 2 through 5.
Keywords: Contracts- Economics aspects